Policies on Joint forest Management and its Implementation in Maharashtra - Jha, Mohan (Indian Forester, 2000)
This paper deals with reshaping of the forest policies in India and its implementation in Maharashtra. Fundamental shift in the forest policies is evident as the role oflocal community is gradually changing from mere beneficiary to the equal partner in management. However one of the largest States like Maharashtra could not keep pace with the rest of the country in implementation of the New Forest Policy. Maharashtra forestry project aided by World Bank could give some boost to the JFM movement in Maharashtra. Flexibility, legal backing and proper institutional framework can help in accelerating the JFM movement.